Energy Consumption Survey on Cloud Environment - Dutta, Neha; Cheema, Pardeep Singh (Journal of Advanced Research in Signal Processing and Applications, 2023)
Today’s users prefer pay-per-use internet services. Cloud computing provides this service. Thus, the use of cloud services has gradually become more widespread. Clouds offer services like file sharing, file storage, data backup. Online database Flexibility reduced administrative burden, scalability. However, there is too much energy use. In the paper, various factors are explained.